Embryonal rhabdomyosarcoma in the sigmoid mesentery - Larbi Benradi; Kamal El Haissoufi; Abdelouhab Ammor; Anas Haloui; Amal Bennani; Driss El Azzouzi; Houssain Benhaddou (Elsevier, 2021)
Rhabdomyosarcoma (RMS) is a malignant tumor that originates from undifferentiated mesenchymal cells and can develop in any anatomic site of the body. It represents the most diagnosed cancer within soft-tissue sarcomas in the paediatric population. The clinical manifestations are non-specific and depend on the location and the size of the tumor. Surgery and chemotherapy represent the two standard therapeutic options for its management. The prognosis of this neoplasm was mainly improved during the last decades and is associated with a number of clinical, surgical and pathological factors. To date, primary RMS arising from the mesentery is rarely seen in the paediatric population and only few cases were reported in the literature. In this paper, we report a successfully managed case of a 2 year-old girl diagnosed with a mesocolon embryonal rhabdomyosarcoma.